Light emitting device, method for manufacturing the same, and display device including the same

By using zinc metal oxide nanoparticles and electron auxiliary layers of small molecule organic compounds in quantum dot light emitting devices, the problems of high leakage current and poor charge balance in the prior art are solved, and more efficient and longer life luminescence performance is achieved.

CN110729404BActive Publication Date: 2025-02-28SAMSUNG ELECTRONICS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN201910644525.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-07-17
Filing Date
2019-07-17
Publication Date
2025-02-28
Estimated Expiration
2039-07-17

AI Technical Summary

Technical Problem

There is room for improvement in performance in existing quantum dot light emitting devices, especially in reducing leakage currents and improving charge balance.

Method used

An electron-transport layer is formed through a solution process using an electron auxiliary layer including zinc metal oxide nanoparticles and small molecule organic compounds to control electron mobility and energy level distribution.

Benefits of technology

It effectively reduces the high leakage current of Zn metal oxide devices, improves the balance between charges, and thus improves the efficiency and life of quantum dot electroluminescent devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN110729404B_ABST
    Figure CN110729404B_ABST
Patent Text Reader

Abstract

A light-emitting device, a manufacturing method thereof, and a display device including the same, wherein the light-emitting device includes: a first electrode and a second electrode facing each other; an emission layer disposed between the first electrode and the second electrode, the emission layer including quantum dots; and an electron-assisting layer disposed between the emission layer and the second electrode, the electron-assisting layer including nanoparticles and a small molecule organic compound. The nanoparticles include a metal oxide containing zinc, and the electron mobility of the small molecule organic compound is less than the electron mobility of the nanoparticles.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to and the benefits of Korean Patent Application No. 10-2018-0083061 filed in the Korean Intellectual Property Office on July 17, 2018, and all rights arising therefrom, the contents of which are incorporated herein by reference in their entirety. Technical Field

[0003] Disclosed are a light emitting device and a display apparatus. Background Art

[0004] Unlike bulk materials, the physical properties of nanoparticles (e.g., band gap, melting point, etc.), which are intrinsic properties, can be controlled by changing the particle size of the nanoparticles. For example, semiconductor nanocrystals, also known as quantum dots, can be supplied with light energy or electrical energy and can emit light of a wavelength corresponding to the size of the quantum dots. Therefore, quantum dots can be used as light-emitting elements that emit light of a specific wavelength. Summary of the invention

[0005] Quantum dots are useful as light emitting devices. However, new methods of improving the performance of light emitting devices including quantum dots are needed.

[0006] Embodiments provide a light emitting device capable of achieving improved performance.

[0007] An embodiment provides a display apparatus including the light emitting device.

[0008] According to an embodiment, a light emitting device includes,

[0009] a first electrode and a second electrode facing each other; an emission layer disposed between the first electrode and the second electrode, the emission layer comprising quantum dots; and an electron-assisted layer disposed between the emission layer and the second electrode, the electron-assisted layer comprising nanoparticles and small molecule organic compounds,

[0010] wherein the nanoparticles include a metal oxide comprising zinc, and

[0011] The electron mobility of the small molecule organic compound is smaller than the electron mobility of the nanoparticles.

[0012] The small molecule organic compound can transport electrons.

[0013] A work function of the first electrode may be greater than a work function of the second electrode.

[0014] The first electrode may include indium tin oxide.

[0015] The second electrode may include a conductive metal.

[0016] The quantum dots may not include cadmium.

[0017] The quantum dots may include indium and phosphorus.

[0018] The quantum dots may include chalcogen and zinc.

[0019] An absolute value of a lowest unoccupied molecular orbital (LUMO) of the quantum dot may be smaller than an absolute value of the LUMO of the metal oxide.

[0020] An absolute value of a lowest unoccupied molecular orbital (LUMO) of the quantum dot may be greater than an absolute value of the LUMO of the metal oxide.

[0021] The metal oxide may include Zn 1-x M x O (wherein M is Mg, Ca, Zr, W, Li, Ti, Y, Al, or a combination thereof, and 0≤x≤0.5).

[0022] The metal oxide may include zinc oxide, zinc magnesium oxide, or a combination thereof.

[0023] The nanoparticles may have an average size greater than or equal to about 1 nanometer (nm).

[0024] The nanoparticles may have an average size of less than or equal to about 10 nm.

[0025] The nanoparticles may have an average size greater than or equal to about 1.5 nm.

[0026] The nanoparticles may have an average size of less than or equal to about 5 nm.

[0027] The small molecule organic compound may have an absolute value of a LUMO energy level of greater than or equal to about 2.5 electron volts (eV) and less than or equal to about 3 eV.

[0028] The electron mobility in the thin film including the small molecule organic compound may be lower than the electron mobility in the thin film including the nanoparticles.

[0029] The small molecule organic compound may include a compound including a triarylphosphine oxide moiety attached to an aromatic ring.

[0030] The small molecule organic compound may include a compound represented by Chemical Formula 2:

[0031] Chemical formula 2

[0032]

[0033] wherein Ar is a substituted or unsubstituted C6-C40 aryl group, a substituted or unsubstituted C3-C40 heteroaryl group, a substituted or unsubstituted C3-C40 heterocycloalkyl group, or a combination thereof, and

[0034] n is an integer from 1 to 10, for example, greater than or equal to 1, greater than or equal to 2, or greater than or equal to 3 and less than or equal to 10, less than or equal to 9, less than or equal to 8, less than or equal to 7, less than or equal to 6, or less than or equal to 5.

[0035] The small molecule organic compound may include a compound represented by Chemical Formula 2-1:

[0036] Chemical formula 2-1

[0037]

[0038] Wherein, Ar is a substituted or unsubstituted C6-C40 aryl group, a substituted or unsubstituted C3-C40 heteroaryl group, a substituted or unsubstituted C3-C40 heterocycloalkyl group, or a combination thereof.

[0039] In the electron assist layer, the content of carbon relative to 1 mol of zinc may be greater than or equal to about 0.01 mol, for example, greater than or equal to about 0.05 mol, or greater than or equal to about 0.1 mol.

[0040] In the electron assist layer, the carbon content relative to 1 mol of zinc may be less than or equal to about 20 mol, for example, less than or equal to about 19 mol, less than or equal to about 18 mol, less than or equal to about 17 mol, less than or equal to about 16 mol, less than or equal to about 15 mol, less than or equal to about 14 mol, less than or equal to about 13 mol, less than or equal to about 12 mol, less than or equal to about 11 mol, less than or equal to about 10 mol, less than or equal to about 9 mol, less than or equal to about 8 mol, less than or equal to about 7 mol, less than or equal to about 6 mol, less than or equal to about 5 mol, less than or equal to about 4 mol, less than or equal to about 3 mol, less than or equal to about 2 mol, less than or equal to about 1 mol, less than or equal to about 0.9 mol, or less than or equal to about 0.8 mol.

[0041] The quantum dots may emit light having a central wavelength of about 600 nm to about 640 nm, and the electron assist layer may have a thickness greater than or equal to about 20 nm and less than or equal to about 70 nm.

[0042] The quantum dots may emit light having a central wavelength of less than or equal to about 500 nm, and the electron assist layer may have a thickness of greater than or equal to about 60 nm and less than or equal to about 100 nm.

[0043] In an embodiment, a method of manufacturing the aforementioned light emitting device includes

[0044] dispersing the nanoparticles and the small molecule organic compound in a polar organic solvent to prepare a dispersion;

[0045] applying the dispersion onto an emissive layer comprising quantum dots to form an electron assisting layer; and

[0046] The polar organic solvent is removed from the electron assisting layer.

[0047] The polar organic solvent may include an alcohol solvent, a sulfoxide solvent, an amide solvent, and the like.

[0048] In the dispersion, the content of the small molecule organic compound based on 100 parts by weight of the nanoparticles may be greater than or equal to about 1 part by weight, for example, greater than or equal to about 5 parts by weight, greater than or equal to about 10 parts by weight, greater than or equal to about 15 parts by weight, or greater than or equal to about 20 parts by weight.

[0049] In the dispersion, the content of the small molecule organic compound relative to 100 parts by weight of the nanoparticles may be less than or equal to about 50 parts by weight, for example, less than or equal to about 45 parts by weight, less than or equal to about 40 parts by weight, less than or equal to about 35 parts by weight, less than or equal to about 30 parts by weight, less than or equal to about 25 parts by weight, or less than or equal to about 20 parts by weight.

[0050] In an embodiment, there is provided a method of manufacturing a light emitting device, the method comprising:

[0051] The ZnO nanoparticles and the small molecule organic compound are dispersed in a polar organic solvent to prepare a dispersion, wherein the small molecule organic compound includes a compound represented by Chemical Formula 2:

[0052] Chemical formula 2

[0053]

[0054] wherein Ar is a substituted or unsubstituted C6-C40 aryl group, a substituted or unsubstituted C3-C40 heteroaryl group, a substituted or unsubstituted C3-C40 heterocycloalkyl group, or a combination thereof, and n is an integer of 1-10; and

[0055] applying the dispersion onto an emissive layer comprising quantum dots to form an electron assisting layer,

[0056] The quantum dots include indium and phosphorus, or chalcogen and zinc, and do not include cadmium.

[0057] An embodiment provides a display apparatus including the aforementioned light emitting device.

[0058] According to embodiments, a high level of leakage current of a device including Zn metal oxide may be effectively reduced, the balance between charges injected into the emission layer may be improved, and thus the efficiency and lifetime of a quantum dot (QD)-based electroluminescent device may be simultaneously improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 is a schematic cross-sectional view of a light emitting device according to an embodiment,

[0060] Figure 2 is the external quantum efficiency (EQE) (percentage (%)) to luminescence (L) (candela / square meter (Cd / m 2 )) showing the electroluminescent properties of the devices according to Example 1 and Comparative Example 1-1,

[0061] Figure 3 is the current density (J) (mA / cm 2 )) versus voltage (volt (V)), which shows the current density-voltage curve (leakage current) of the devices according to Example 1 and Comparative Example 1-1,

[0062] Figure 4 is the external quantum efficiency (%) to luminescence (Cd / m 2 ) showing the electroluminescent properties of the devices according to Example 2 and Comparative Example 2-1,

[0063] Figure 5 is the current density (mA / cm 2 ) versus voltage (V), which shows the current density-voltage curves (leakage current) of the devices according to Example 2 and Comparative Example 2-1, and

[0064] Figure 6 is the external quantum efficiency (%) to luminescence (Cd / m 2 ) showing the electroluminescent properties of the devices according to Comparative Example 2-2 and Comparative Example 2-3.

[0065] Figure 7 is an energy band diagram of a device according to one embodiment, wherein the energy level arrangement for each layer can represent the energy level relationship of a given device.

[0066] Figure 8 is an energy band diagram of a device according to another embodiment, wherein the energy level arrangement for each layer can represent the energy level relationship of a given device. DETAILED DESCRIPTION

[0067] Hereinafter, example embodiments of the present disclosure will be described in detail so that those skilled in the art will understand it. However, the present disclosure may be embodied in many different forms and is not to be construed as limited to the example embodiments set forth herein.

[0068] In the accompanying drawings, the thickness of layers, films, panels, regions, etc. is exaggerated for clarity. Throughout the specification, the same reference numerals represent the same elements. It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it may be directly on the other element or there may be an intermediate element. On the contrary, when an element is referred to as being "directly on" another element, there is no intermediate element.

[0069] It will be understood that although the terms "first", "second", "third", etc. may be used herein to describe various elements, components, regions, layers and / or parts, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or part from another element, component, region, layer or part. Therefore, without departing from the teachings herein, the "first element", "component", "region", "layer" or "part" discussed below may be referred to as a second element, component, region, layer or part.

[0070] The terms used herein are only for the purpose of describing specific embodiments and are not intended to be restrictive. As used herein, the singular forms "one (kind) (indefinite article, a, an)" and "the (the)" are intended to include plural forms, including "at least one (kind)", unless the content clearly indicates otherwise. "At least one (kind)" is not interpreted as limiting "one (kind)". "Or" means "and / or". As used herein, the term "and / or" includes any and all combinations of one or more of the related enumerated items. It will be further understood that the term "comprising" or "including" when used in this specification indicates that there are stated features, regions, wholes, steps, operations, elements, and / or components, but does not exclude the presence or increase of one or more other features, regions, wholes, steps, operations, elements, components, and / or their sets.

[0071] As used herein, "about" includes the stated value and means within an acceptable range of deviation for a particular value as determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" may mean that the deviation from the stated value is within one or more standard deviations, or within a range of ±30%, 20%, 10%, or 5%.

[0072] Unless otherwise defined, all terms (including technical and scientific terms) used in this article have the same meaning as commonly understood by ordinary technicians in the field to which the present disclosure belongs. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as their meanings consistent with their meanings in the context of the present disclosure and the relevant art, and will not be interpreted in an idealized or overly formal sense unless clearly defined in this article.

[0073] Exemplary embodiments are described herein with reference to cross-sectional views as schematic diagrams of idealized embodiments. Thus, deviations from the shapes of the figures as a result of, for example, manufacturing techniques and / or tolerances are expected. Thus, the embodiments described herein should not be construed as being limited to the specific shapes of the regions as shown herein, but rather include deviations in shape resulting from, for example, manufacturing. For example, a region illustrated or described as flat may typically have rough and / or nonlinear features. In addition, the illustrated sharp corners may be rounded. Thus, the regions shown in the figures are schematic in nature, and their shapes are not intended to illustrate the precise shapes of the regions, and are not intended to limit the scope of the claims.

[0074] Hereinafter, the work function or the highest occupied molecular orbital (HOMO) energy level is expressed as an absolute value from the vacuum energy level. In addition, when the work function or the HOMO energy level is referred to as "deep", "high" or "large", the work function or the HOMO energy level has a large absolute value based on the vacuum energy level "0 eV", and when the work function or the HOMO energy level is referred to as "shallow", "low" or "small", the work function or the HOMO energy level has a small absolute value based on the vacuum energy level "0 eV".

[0075] As used herein, LUMO, HOMO and / or work function can be measured using a suitable method, which is not particularly limited. In an embodiment, the LUMO, HOMO and / or work function of a given material can be measured by cyclic voltammetry (CV) method, spectroscopic analysis (e.g., ultraviolet photoelectron spectroscopy (UPS) method and / or UV-Vis spectroscopy), photoelectron spectroscopy in air (e.g., using AC-3), Kelvin Probe force microscopy measurement, or a combination thereof.

[0076] As used herein, the term "Group" may refer to a Group of the periodic table.

[0077] As used herein, “Group I” may refer to Group IA and Group IB, and examples may include Li, Na, K, Rb, and Cs, but are not limited thereto.

[0078] As used herein, “Group II” may refer to Group IIA and Group IIB, and examples of Group II metals may be Cd, Zn, Hg, and Mg, but are not limited thereto.

[0079] As used herein, “Group III” may refer to Group IIIA and Group IIIB, and examples of Group III metals may be Al, In, Ga, and Tl, but are not limited thereto.

[0080] As used herein, "Group IV" may refer to Group IVA and Group IVB, and examples of Group IV metals may be Si, Ge, and Sn, but are not limited thereto. As used herein, the term "metal" may include semimetals such as Si.

[0081] As used herein, “Group V” may refer to Group VA, and examples may include nitrogen, phosphorus, arsenic, antimony, and bismuth, but are not limited thereto.

[0082] As used herein, "Group VI" may refer to Group VIA, and examples may include sulfur, selenium, and tellurium, but are not limited thereto.

[0083] As used herein, when no definition is otherwise provided, "substituted" refers to a compound, group, or moiety where hydrogen is replaced by a C1-C30 alkyl, C2-C30 alkenyl, C2-C30 alkynyl, C2-C30 epoxy, C2-C30 alkyl ester, C3-C30 alkenyl ester (e.g., acrylate, methacrylate), C6-C30 aryl, C7-C30 alkaryl, C1-C30 alkoxy, C1-C30 heteroalkyl, C3-C40 heteroaryl, C3-C30 heteroalkaryl, C3-C30 cycloalkyl, C3-C15 cycloalkenyl, C6-C30 cycloalkynyl, C2-C30 heterocycloalkyl, halogen (-F, -Cl, -Br, or -I), hydroxyl (-OH), nitro (-NO), or 2 ), cyano (-CN), amino (-NRR', wherein R and R' are independently hydrogen or C1-C6 alkyl), azido (-N 3 ), amidino (-C(=NH)NH 2 ), hydrazino (-NHNH 2 ), hydrazone (=N(NH 2 )), aldehyde group (-C(=O)H), carbamoyl group (-C(O)NH 2 ), thiol group (-SH), ester group (-C(=O)OR, wherein R is C1-C6 alkyl or C6-C12 aryl), carboxyl group (-COOH) or its salt (-C(=O)OM, wherein M is an organic or inorganic cation), sulfonic acid group (-SO 3 H) or its salt (-SO 3 M, where M is an organic or inorganic cation), a phosphate group (-PO 3 H 2 ) or its salt (-PO 3 MH or -PO 3 M2 , wherein M is an organic or inorganic cation), or a combination thereof.

[0084] As used herein, when no definition is otherwise provided, "aliphatic" refers to a C1-C40 linear or branched hydrocarbon (eg, alkyl, alkenyl, or alkynyl) group.

[0085] As used herein, when a definition is not otherwise provided, "alkoxy" refers to an alkyl group linked through an oxygen group (ie, alkyl-O-), for example, methoxy, ethoxy, and sec-butoxy.

[0086] As used herein, when a definition is not otherwise provided, "alkyl" refers to a linear or branched, saturated, monovalent (eg, C1-C40) hydrocarbon group (eg, methyl or ethyl).

[0087] As used herein, when a definition is not otherwise provided, "alkylene" refers to a linear or branched saturated (eg, C2-C40) aliphatic hydrocarbon group having a valence of at least 2 and optionally substituted with at least one substituent.

[0088] As used herein, when a definition is not otherwise provided, "alkynyl" refers to a straight or branched monovalent (eg, C2-C40) hydrocarbon group (eg, ethynyl) having at least one carbon-carbon triple bond.

[0089] As used herein, when no definition is otherwise provided, an "amine" group has the general formula -NRR, wherein each R is independently hydrogen, C1-C12 alkyl, C7-C20 alkaryl, C7-C20 aralkyl, or C6-C18 aryl.

[0090] As used herein, when no definition is otherwise provided, "aromatic hydrocarbons" refer to hydrocarbons having an aromatic ring, and include monocyclic and polycyclic hydrocarbons, wherein the additional rings of the polycyclic hydrocarbons are aromatic or non-aromatic. Specific aromatic hydrocarbons may include benzene, naphthalene, toluene, and xylene.

[0091] As used herein, when no definition is otherwise provided, "aromatic" refers to an organic compound or group that includes at least one unsaturated cyclic group having delocalized π electrons. The term includes both hydrocarbon aromatic compounds and heteroaromatic compounds.

[0092] As used herein, when a definition is not otherwise provided, "aryl" refers to a hydrocarbon group having a valence of at least one (eg, phenyl or naphthyl), such as formed by removing at least one hydrogen atom from one or more rings of an aromatic hydrocarbon.

[0093] As used herein, when a definition is not otherwise provided, "aralkyl" refers to a substituted or unsubstituted aryl group covalently linked to an alkyl group (the alkyl group is linked to the compound) (eg, benzyl is a C7 aralkyl group).

[0094] As used herein, when a definition is not otherwise provided, "arylene" refers to a functional group having a valence of at least 2 obtained by removing at least two hydrogens in at least one aromatic ring, which is optionally substituted with at least one substituent.

[0095] As used herein, when a definition is not otherwise provided, "cycloalkenyl" refers to a monovalent hydrocarbon group having one or more rings and one or more carbon-carbon double bonds in the rings, wherein all ring members are carbon (eg, cyclopentenyl and cyclohexenyl).

[0096] As used herein, when a definition is not otherwise provided, "cycloalkyl" refers to a hydrocarbon group having one or more saturated rings and having a valence of at least one, wherein all ring members are carbon (eg, cyclopentyl and cyclohexyl).

[0097] As used herein, when a definition is not otherwise provided, "cycloalkynyl" refers to a stable aliphatic monocyclic or polycyclic group having at least one carbon-carbon triple bond, wherein all ring members are carbon (eg, cyclohexynyl).

[0098] As used herein, when no additional definition is provided, "ester" refers to a group of formula -O(C=O)Rx or a group of formula -(C=O)ORx, wherein Rx is a C1-C28 aromatic organic group or an aliphatic organic group. Ester groups include C2-C30 ester groups, and particularly C2-C18 ester groups.

[0099] As used herein, when no definition is otherwise provided, the term "hetero" means including at least one to three heteroatoms, wherein the heteroatoms may be N, O, S, Si or P, preferably N, O or S.

[0100] As used herein, when no definition is otherwise provided, "heteroalkyl" refers to an alkyl group that includes at least one heteroatom covalently bonded to one or more carbon atoms of the alkyl group.

[0101] As used herein, when a definition is not otherwise provided, "heteroaryl" refers to an aromatic group (or aryl group) that includes at least one heteroatom bonded to one or more carbon atoms of an aromatic ring.

[0102] Hereinafter, a light emitting device according to an embodiment is described with reference to the accompanying drawings.

[0103] Figure 1 is a schematic cross-sectional view of a light emitting device according to an embodiment.

[0104] Reference Figure 1According to the embodiment, the light emitting device 10 includes a first electrode 11 and a second electrode 15 facing each other, an emission layer 13 disposed between the first electrode 11 and the second electrode 15 and including quantum dots, a hole auxiliary layer 12 disposed between the first electrode 11 and the emission layer 13, and an electron auxiliary layer 14 disposed between the second electrode 15 and the emission layer 13.

[0105] The substrate may be disposed on the main surface of the first electrode 11 or on the main surface of the second electrode 15. In an embodiment, the substrate may be disposed on the main surface of the first electrode. The substrate may be a substrate including an insulating material (e.g., an insulating transparent substrate). The substrate may include: glass; various polymers such as polyesters (e.g., polyethylene terephthalate (PET), polyethylene naphthalate (PEN)), polycarbonate, polyacrylate, polyimide, and polyamideimide; polysiloxane (e.g., PDMS); inorganic materials such as Al 2 O 3 and ZnO; or a combination thereof, but not limited thereto. The substrate may be made of a silicon wafer. Here, "transparent" may refer to a transmittance of greater than or equal to about 85%, such as greater than or equal to about 88%, greater than or equal to about 90%, greater than or equal to about 95%, greater than or equal to about 97%, or greater than or equal to about 99% for light of a predetermined wavelength (e.g., light emitted from quantum dots). The thickness of the substrate may be appropriately selected in consideration of the substrate material without particular limitation. The transparent substrate may be flexible. The substrate may be omitted.

[0106] One of the first electrode 11 and the second electrode 15 may be an anode and the other may be a cathode. For example, the first electrode 11 may be an anode and the second electrode 15 may be a cathode.

[0107] The first electrode 11 may be made of a conductor such as a metal, a conductive metal oxide, or a combination thereof. The first electrode 11 may be made of, for example, a metal or an alloy thereof such as nickel, platinum, vanadium, chromium, copper, zinc, and gold; a conductive metal oxide such as zinc oxide, indium oxide, tin oxide, indium tin oxide (ITO), indium zinc oxide (IZO), or fluorine-doped tin oxide; or a metal and a metal oxide such as ZnO and Al or SnO 2 In an embodiment, the first electrode may include a transparent conductive metal oxide such as indium tin oxide. The work function of the first electrode may be higher than the work function of the second electrode to be described later.

[0108] The second electrode 15 can be made of a conductor such as a metal, a conductive metal oxide, a conductive polymer, or a combination thereof. The second electrode 15 can be, for example, a metal or an alloy thereof such as aluminum, magnesium, calcium, sodium, potassium, titanium, indium, yttrium, lithium, gadolinium, silver, tin, lead, cesium, or barium; a multilayer structure of materials such as LiF / Al, Li2 O / Al, Liq / Al, LiF / Ca, and BaF 2 / Ca, but not limited thereto. The conductive metal oxide is the same as described above.

[0109] In an embodiment, the work function of the first electrode 11 may be greater than or equal to about 4.0 eV, greater than or equal to about 4.1 eV, greater than or equal to about 4.2 eV, greater than or equal to about 4.3 eV, greater than or equal to about 4.4 eV, or greater than or equal to about 4.5 eV and less than or equal to about 5.0 eV, for example, less than or equal to about 4.9 eV, and the work function of the second electrode 15 may be, for example, greater than or equal to about 4.0 eV and less than about 4.5 eV. Within the range, the work function of the first electrode 11 may be, for example, about 4.6 eV-about 4.9 eV, and the work function of the second electrode 15 may be, for example, about 4.0 eV-about 4.3 eV.

[0110] At least one of the first electrode 11 and the second electrode 15 may be a light-transmitting electrode, and the light-transmitting electrode may be made of, for example, a conductive oxide such as zinc oxide, indium oxide, tin oxide, indium tin oxide (ITO), indium zinc oxide (IZO), or fluorine-doped tin oxide, or a single or multiple metal thin layers. When one of the first electrode 11 and the second electrode 15 is a non-light-transmitting electrode, the non-light-transmitting electrode may be made of, for example, an opaque conductor such as aluminum (Al), silver (Ag), or gold (Au).

[0111] The thickness of the electrode (the first electrode, the second electrode, or a combination thereof) is not particularly limited and may be appropriately selected in consideration of device efficiency. For example, the thickness of the electrode may be greater than or equal to about 5 nm, for example, greater than or equal to about 50 nm. For example, the thickness of the electrode may be less than or equal to about 100 micrometers (μm), for example, 10 μm, less than or equal to about 1 μm, less than or equal to about 900 nm, less than or equal to about 500 nm, or less than or equal to about 100 nm.

[0112] The emission layer 13 includes (e.g., multiple) quantum dots. The quantum dots (hereinafter, also referred to as semiconductor nanocrystals) may include II-VI compounds, III-V compounds, IV-VI compounds, IV elements or compounds, I-III-VI compounds, II-III-VI compounds, I-II-IV-VI compounds, or combinations thereof.

[0113] The II-VI group compound may be a binary compound such as CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, MgSe, MgS, or a combination thereof; a ternary compound such as CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe , CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, MgZnSe, MgZnS, or a combination thereof; and quaternary compounds such as HgZnTeS, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe, or a combination thereof; or a combination thereof. The II-VI group compound may further include a Group III metal. The III-V compound may be a binary compound such as GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, or a combination thereof; a ternary compound such as GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, or a combination thereof; and a quaternary compound such as GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb, InZnP, or a combination thereof; or a combination thereof. The III-V compound may further include a Group II metal (e.g., InZnP). The IV-VI group compound may be a binary compound such as SnS, SnSe, SnTe, PbS, PbSe, PbTe, or a combination thereof; a ternary compound such as SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, or a combination thereof; and a quaternary compound such as SnPbSSe, SnPbSeTe, SnPbSTe, or a combination thereof; or a combination thereof. Examples of the I-III-VI group compound may include CuInSe 2 、CuInS 2, CuInGaSe, and CuInGaS, but not limited thereto. Examples of the I-II-IV-VI group compound may include CuZnSnSe and CuZnSnS, but not limited thereto. The IV group element or compound may be: a simple substance, such as Si, Ge, or a combination thereof; and a binary compound, such as SiC, SiGe, or a combination thereof; or a combination thereof.

[0114] In an embodiment, the quantum dot may not include cadmium. The quantum dot may include a semiconductor nanocrystal based on a III-V compound including indium and phosphorus. The III-V compound may further include zinc. The quantum dot may include a semiconductor nanocrystal based on a II-VI compound including a chalcogen (e.g., sulfur, selenium, tellurium, or a combination thereof) and zinc.

[0115] In the quantum dot, the aforementioned binary compound, ternary compound, quaternary compound or a combination thereof are present in the semiconductor nanocrystal particles with uniform concentrations or in the same particles with locally different concentrations. The semiconductor nanocrystal may have a core / shell structure, wherein a first semiconductor nanocrystal (core) is surrounded by another second semiconductor nanocrystal (shell) having the same or different composition as the core. In an embodiment, the quantum dot may include a core and a shell (or multilayer shell), the core including InP, InZnP, ZnSe, ZnSeTe or a combination thereof, the shell (or multilayer shell) having a composition different from the core and including InP, InZnP, ZnSe, ZnS, ZnSeTe, ZnSeS or a combination thereof.

[0116] The core and the shell may have an interface, and at least one of the elements of the core or the shell in the interface may have a concentration gradient, wherein the concentration of the element of the shell decreases toward the core. The semiconductor nanocrystal may have a structure comprising a semiconductor nanocrystal core and a multilayer shell around it. Here, the multilayer shell has at least two layers of shells, wherein each shell may be a single composition, may be an alloy, may have a concentration gradient, or a combination thereof.

[0117] In the quantum dot, the shell material and the core material may have different band gaps from each other. For example, the band gap of the shell material may be greater than the band gap of the core material. According to an embodiment, the band gap of the shell material may be smaller than the band gap of the core material. The quantum dot may have a multilayer shell. In the multilayer shell, the band gap of the outer layer may be greater than the band gap of the inner layer (i.e., the layer closer to the core). In the multilayer shell, the band gap of the outer layer may be smaller than the band gap of the inner layer.

[0118] The quantum dots can control the absorption / photoluminescence wavelength by adjusting the composition and size. The maximum photoluminescence peak wavelength of the quantum dots can be ultraviolet (UV) to infrared wavelengths or wavelengths greater than the above wavelength range. For example, the maximum photoluminescence peak wavelength of the quantum dots can be greater than or equal to about 300nm, such as greater than or equal to about 500nm, greater than or equal to about 510nm, greater than or equal to about 520nm, greater than or equal to about 530nm, greater than or equal to about 540nm, greater than or equal to about 550nm, greater than or equal to about 560nm, greater than or equal to about 570nm, greater than or equal to about 580nm, greater than or equal to about 590nm, greater than or equal to about 600nm, or greater than or equal to about 610nm. The maximum photoluminescence wavelength of the quantum dot may be less than or equal to about 800 nm, such as less than or equal to about 650 nm, less than or equal to about 640 nm, less than or equal to about 630 nm, less than or equal to about 620 nm, less than or equal to about 610 nm, less than or equal to about 600 nm, less than or equal to about 590 nm, less than or equal to about 580 nm, less than or equal to about 570 nm, less than or equal to about 560 nm, less than or equal to about 550 nm, or less than or equal to about 540 nm. The maximum photoluminescence wavelength of the quantum dot may be in the range of about 500 nm to about 650 nm. The maximum photoluminescence wavelength of the quantum dot may be in the range of about 500 nm to about 540 nm. The maximum photoluminescence wavelength of the quantum dot may be in the range of about 610 nm to about 640 nm.

[0119] The quantum dots may have a quantum efficiency of about 10% or more, such as about 30% or more, about 50% or more, about 60% or more, about 70% or more, about 90% or more, or even about 100%. The quantum dots may have a relatively narrow spectrum. The quantum dots may have a half width (FWHM) of a photoluminescence wavelength spectrum of, for example, about 50 nm or less, such as about 45 nm or less, about 40 nm or less, or about 30 nm or less.

[0120] The quantum dots may have a particle size (e.g., diameter or maximum straight length across the particle) greater than or equal to about 1 nm and less than or equal to about 100 nm. The quantum dots may have an (average) particle size of about 1 nm to about 50 nm, such as greater than or equal to about 2 nm, greater than or equal to about 3 nm, or greater than or equal to about 4 nm and less than or equal to about 50 nm, less than or equal to about 40 nm, less than or equal to about 30 nm, less than or equal to about 20 nm, less than or equal to about 15 nm, or less than or equal to about 10 nm. The shape of the quantum dots is not particularly limited. For example, the shape of the quantum dots may be a sphere, a polyhedron, a pyramid, a multi-legged (multi-pod), a square, a cuboid, a nanotube, a nanorod, a nanowire, a nanosheet, or a combination thereof, but is not limited thereto.

[0121] In embodiments, the particle size (e.g., for quantum dots or for metal oxide particles) may be measured by analysis using electron microscopy (e.g., TEM). In embodiments, the particle size may be measured from a two-dimensional image obtained by an electron microscope (e.g., by calculation using a commercial image analysis program such as Image J). In embodiments, the particle size (e.g., for quantum dots or for metal oxide particles) may be an average (e.g., mean, mode, or median average) size. Average may be mean, mode, or median average.

[0122] The quantum dots may be commercially available or may be suitably synthesized. When the quantum dots are colloidally synthesized, the particle size may be controlled relatively freely and also uniformly.

[0123] The quantum dot may include an organic ligand (e.g., having a hydrophobic portion). The organic ligand portion may be bound to the surface of the quantum dot. The organic ligand may include RCOOH, RNH 2 , R 2 NH, R 3 N, RSH, R 3 PO, R 3 P, ROH, RCOOR, RPO(OH) 2 , RHPOOH, R 2 POOH, or a combination thereof, wherein each R is independently a C3 (e.g., C5)-C24 substituted or unsubstituted aliphatic hydrocarbon group, such as a C3-C24 alkyl or alkenyl group, a C6-C20 substituted or unsubstituted aromatic hydrocarbon group, such as a C6-C20 aryl group, or a combination thereof.

[0124] Examples of the organic ligand may be: a thiol compound such as methyl mercaptan, ethyl mercaptan, propyl mercaptan, butyl mercaptan, pentyl mercaptan, hexyl mercaptan, octyl mercaptan, dodecanethiol, hexadecyl mercaptan, octadecyl mercaptan, or benzyl mercaptan; an amine compound such as methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, octylamine, nonylamine, decylamine, dodecylamine, hexadecylamine, octadecylamine, dimethylamine, diethylamine, dipropylamine, tributylamine, or trioctylamine; a carboxylic acid compound such as formic acid, acetic acid, propionic acid, butyric acid, pentanoic acid, hexanoic acid, heptanoic acid, octanoic acid, dodecanoic acid, hexadecanoic acid, octadecanoic acid, oleic acid, or benzoic acid; a phosphine compound such as methylphosphine , ethylphosphine, propylphosphine, butylphosphine, pentylphosphine, octylphosphine, dioctylphosphine, tributylphosphine, diphenylphosphine, triphenylphosphine, trioctylphosphine; phosphine oxide compounds such as methylphosphine oxide, ethylphosphine oxide, propylphosphine oxide, butylphosphine oxide, pentylphosphine oxide, tributylphosphine oxide, octylphosphine oxide, dioctylphosphine oxide, diphenylphosphine oxide, triphenylphosphine oxide, or trioctylphosphine oxide; C5-C20 alkylphosphonic acid; C5-C20 alkylphosphinic acid such as hexylphosphinic acid, octylphosphinic acid, dodecanephosphinic acid, tetradecanephosphinic acid, hexadecanephosphinic acid, octadecanephosphinic acid; etc., but not limited thereto. The quantum dots may include hydrophobic organic ligands alone or in the form of a mixture of at least one type. The hydrophobic organic ligands may not include a photopolymerizable portion (e.g., an acrylate group, a methacrylate group, etc.).

[0125] In an embodiment, the emission layer 13 may include a monolayer of quantum dots. In an embodiment, the emission layer 13 may include at least one monolayer of quantum dots, for example, 2 or more monolayers, 3 or more monolayers, or 4 or more monolayers, and 20 or less monolayers, 10 or less monolayers, 9 or less monolayers, 8 or less monolayers, 7 or less monolayers, or 6 or less monolayers. The emission layer 13 may have a thickness greater than or equal to about 5 nm, for example, greater than or equal to about 10 nm, greater than or equal to about 20 nm, or greater than or equal to about 30 nm and less than or equal to about 200 nm, for example, less than or equal to about 150 nm, less than or equal to about 100 nm, less than or equal to about 90 nm, less than or equal to about 80 nm, less than or equal to about 70 nm, less than or equal to about 60 nm, or less than or equal to about 50 nm. The emission layer 13 may have a thickness of, for example, about 10 nm to about 150 nm, for example, about 10 nm to about 100 nm, for example, about 10 nm to about 50 nm.

[0126] The emission layer 13 may have a HOMO energy level of about 5.4 eV or more, about 5.6 eV or more, about 5.7 eV or more, about 5.8 eV or more, about 5.9 eV or more, or about 6.0 eV or more. The emission layer 13 may have a HOMO energy level of about 7.0 eV or less, about 6.8 eV or less, about 6.7 eV or less, about 6.5 eV or less, about 6.3 eV or less, or about 6.2 eV or less. In an embodiment, the emission layer 13 may have a HOMO energy level of about 5.6 eV to about 6.0 eV.

[0127] The emission layer 13 may have, for example, a LUMO energy level of about 3.8 eV or less, about 3.7 eV or less, about 3.6 eV or less, about 3.5 eV or less, about 3.4 eV or less, about 3.3 eV or less, about 3.2 eV or less, or about 3.0 eV or less. The emission layer 13 may have a LUMO energy level of about 2.5 eV or more. In an embodiment, the emission layer 13 may have an energy band gap of about 2.4 eV to about 2.9 eV.

[0128] The hole auxiliary layer 12 is disposed between the first electrode 11 and the emission layer 13. The hole auxiliary layer 12 may have one layer or two or more layers and may include, for example, a hole injection layer (HIL), a hole transport layer (HTL), an electron blocking layer, or a combination thereof.

[0129] The hole assisting layer 12 may have a HOMO energy level that may match the HOMO energy level of the emission layer 13 and may forcibly, for example, assist the migration of holes from the hole assisting layer 12 into the emission layer 13 .

[0130] The HOMO energy level of the hole-assisting layer 12 (e.g., hole transport layer (HTL)) contacting the emission layer may be the same as the HOMO energy level of the emission layer 13 or less than the HOMO energy level of the emission layer 13 in the following range: less than or equal to about 1.0 eV. For example, the difference in HOMO energy level between the hole-assisting layer 12 and the emission layer 13 may be about 0 eV-about 1.0 eV, such as about 0.01 eV-about 0.8 eV, about 0.01 eV-about 0.7 eV, about 0.01 eV-about 0.5 eV, about 0.01 eV-about 0.4 eV, about 0.01 eV-about 0.3 eV, about 0.01 eV-about 0.2 eV, or about 0.01 eV-about 0.1 eV.

[0131] The HOMO energy level of the hole assisting layer 12 may be, for example, greater than or equal to about 5.0 eV, for example, greater than or equal to about 5.2 eV, greater than or equal to about 5.4 eV, greater than or equal to about 5.6 eV, or greater than or equal to about 5.8 eV.

[0132] For example, the HOMO energy level of the hole assisting layer 12 may be about 5.0 eV to about 7.0 eV, about 5.2 eV to 6.8 eV, about 5.4 eV to about 6.8 eV, about 5.4 eV to about 6.7 eV, about 5.4 eV to about 6.5 eV, about 5.4 eV to about 6.3 eV, about 5.4 eV to about 6.2 eV, about 5.4 eV to about 6.1 eV, about 5.6 eV to about 7.0 eV, about 5.6 eV to about 6.8 eV, about 5.6 eV to about 6.7 eV, about 5.6 eV to about 6.5 eV, about 5.6 eV to about 6.3 eV, about 5.6 eV to about 6.2 eV, about 5.6 eV to about 6.1 eV, about 5.8 eV to about 7.0 eV, about 5.8 eV to about 6.8 eV, about 5.8 eV to about 6.7 eV, about 5.8 eV to about 6.5 eV, about 5.8 eV to about 6.3 eV, about 5.8 eV to about 6.2 eV, or about 5.8 eV to about 6.1 eV.

[0133] In an embodiment, the hole auxiliary layer 12 may include a hole injection layer close to the first electrode 11 and a hole transport layer close to the emission layer 13. Here, the HOMO energy level of the hole injection layer may be about 5.0 eV to about 6.0 eV, for example, about 5.0 eV to about 5.5 eV, or about 5.0 eV to about 5.4 eV, and the HOMO energy level of the hole transport layer may be about 5.2 eV to about 7.0 eV, about 5.4 eV to about 6.8 eV, about 5.4 eV to about 6.7 eV, about 5.4 eV to about 6.5 eV, about 5.4 eV to about 6.3 eV, about 5.4 eV to about 6.2 eV, or about 5.4 eV to about 6.1 eV.

[0134] The material included in the hole auxiliary layer 12 is not particularly limited, and may include, for example, at least one of poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine) (TFB), polyarylamine (polyarylamine), poly(N-vinylcarbazole), poly(3,4-ethylenedioxythiophene) (PEDOT), poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), polyaniline, polypyrrole, N,N,N′,N′-tetrakis (4-methoxyphenyl)-benzidine (TPD), 4,4'-di[N-(1-naphthyl)-N-phenyl-amino]biphenyl (α-NPD), m-MTDATA (4,4',4"-tri[phenyl(m-tolyl)amino]triphenylamine), 4,4',4"-tri(N-carbazolyl)-triphenylamine (TCTA), 1,1-di[(di-4-tolylamino)phenyl]cyclohexane (TAPC), p-type metal oxides (e.g., NiO, WO 3 、MoO 3etc.), carbon-based materials such as graphene oxide, and combinations thereof, but are not limited thereto.

[0135] In the hole auxiliary layer, the thickness of each layer can be appropriately selected. For example, the thickness of each layer can be greater than or equal to about 10 nm, such as greater than or equal to about 15 nm, greater than or equal to about 20 nm and less than or equal to about 100 nm, such as less than or equal to about 90 nm, less than or equal to about 80 nm, less than or equal to about 70 nm, less than or equal to about 60 nm, or less than or equal to about 50 nm, but is not limited thereto.

[0136] The electron assist layer 14 is disposed between the emission layer 13 and the second electrode 15. The electron assist layer 14 may include, for example, an electron injection layer, an electron transport layer, a hole blocking layer, or a combination thereof, but is not limited thereto.

[0137] The electron auxiliary layer 14 may be an electron transport layer. The electron auxiliary layer 14 includes nanoparticles and small molecule organic compounds. The nanoparticles include metal oxides containing zinc. The small molecule organic compounds include carbon. The small molecule organic compounds may include compounds capable of transporting electrons. The electron mobility of the small molecule organic compound is less than the electron mobility of the nanoparticles.

[0138] The metal oxide may include a metal oxide of Chemical Formula 1:

[0139] Zn 1-x M x O

[0140] Wherein, in Chemical Formula 1, M is Mg, Ca, Zr, W, Li, Ti, Y, Al, or a combination thereof, and 0≤x≤0.5. In an embodiment, in Chemical Formula 1, M may be magnesium (Mg). In an embodiment, in Chemical Formula 1, x may be greater than or equal to about 0.01 and less than or equal to about 0.3, for example, less than or equal to about 0.15.

[0141] The metal oxide may include zinc oxide, zinc magnesium oxide, or a combination thereof.

[0142] The average size of the nanoparticles may be greater than or equal to about 1 nm, such as greater than or equal to about 1.5 nm, greater than or equal to about 2 nm, greater than or equal to about 2.5 nm, or greater than or equal to about 3 nm and less than or equal to about 10 nm, less than or equal to about 9 nm, less than or equal to about 8 nm, less than or equal to about 7 nm, less than or equal to about 6 nm, or less than or equal to about 5 nm. The nanoparticles may not have a rod shape, or a nanowire shape.

[0143] The absolute value of the lowest unoccupied molecular orbital (LUMO) of the quantum dot may be smaller than the absolute value of the LUMO of the metal oxide. The absolute value of the lowest unoccupied molecular orbital (LUMO) of the quantum dot may be greater than the absolute value of the LUMO of the metal oxide.

[0144] The absolute value of the LUMO of the metal oxide may be greater than or equal to about 2 eV, greater than or equal to about 2.5 eV, greater than or equal to about 3 eV, greater than or equal to about 3.5 eV, or greater than or equal to about 4 eV and less than or equal to about 5 eV, less than or equal to about 4.5 eV, less than or equal to about 4 eV, less than or equal to about 3.5 eV, or less than or equal to about 3 eV.

[0145] The absolute value of the HOMO of the metal oxide may be greater than or equal to about 5 eV, greater than or equal to about 5.5 eV, greater than or equal to about 6 eV, greater than or equal to about 6.5 eV, or greater than or equal to about 7 eV and less than or equal to about 8 eV, less than or equal to about 7.5 eV, less than or equal to about 7 eV, less than or equal to about 6.5 eV, or less than or equal to about 6 eV.

[0146] The energy band gap of the metal oxide may be greater than or equal to about 2 eV, greater than or equal to about 2.5 eV, greater than or equal to about 3 eV, greater than or equal to about 3.5 eV, or greater than or equal to about 4 eV and less than or equal to about 5 eV, less than or equal to about 4.5 eV, less than or equal to about 4 eV, less than or equal to about 3.5 eV, or less than or equal to about 3 eV.

[0147] In a (electroluminescent) QD-light-emitting device, holes and electrons injected from the anode and cathode, respectively, each pass through a common layer (e.g., electron auxiliary layers such as EIL and ETL and hole auxiliary layers such as HIL and HTL) and meet in an emission layer including quantum dots to form excitons and then recombine to emit light. (See Figure 7 and Figure 8 )

[0148] A common layer between the emission layer and the electrodes (anode and cathode) may be required to ensure, for example, help smooth (smooth) transport of holes and electrons when a voltage is applied. The improved electron mobility of an electron auxiliary layer, such as an electron transport layer, can ensure, for example, help hole-electron balance in the emission layer, which may be necessary for efficient electron transport from the electrode to the quantum dot emission layer. In addition, holes transmitted from the quantum dot emission layer may be blocked by the energy level (e.g., HOMO) of the electron auxiliary layer.

[0149] The inventors have found that when a quantum dot light-emitting device includes an electron transport layer based on a metal oxide containing Zn, electrons are more dominant than holes for transferring charge from the cathode to the QD-LED emission layer. Without being bound by any theory, it is believed that the electron transport layer based on Zn metal oxide can show enhanced electron transport capabilities (e.g., high electron injection properties and electron mobility), while quantum dot-based electroluminescent devices show slow hole transport properties.

[0150] Excess electrons relative to the injected holes may flow in the light-emitting device, hole-electron balance may not be guaranteed, for example, to be achieved, and the luminous efficiency of the device may deteriorate. Electrons may accumulate at the interface between the hole transport layer (HTL) and the quantum dot emission layer. The excess electrons may cause interface degradation and may be lost during passage through the interface, which may cause an increase in the number of non-luminescent charges and lead to a deterioration in the life and performance of the QD-LED. Therefore, the electron auxiliary layer based on nanoparticles including Zn metal oxide may exhibit a high level of leakage current, it may be difficult to ensure, for example, that hole-electron balance is achieved, and it may be difficult to achieve efficiency improvement and life extension in quantum dot-based devices.

[0151] Since some of the electron transport layers based on organic materials may exhibit a low LUMO energy level and low electron mobility, smooth electron injection may be difficult to achieve, and charges may be accumulated in the device, which may cause a reduction in the lifetime of the device.

[0152] The light-emitting device according to the embodiment has an electron-assisted layer including a mixture of nanoparticles containing metal oxides and small molecule organic compounds (e.g., having electron transport capability and also having an electron mobility lower than that of the nanoparticles containing the aforementioned metal oxides). The mixed electron-assisted layer can cause effective exciton bonding of holes-electrons to improve efficiency and minimize interfacial accumulation and loss of electrons, so the life of the light-emitting device can be improved.

[0153] According to an embodiment, the small molecule organic compound is a material having lower mobility than the metal oxide including zinc but capable of transporting charges (electrons or holes).

[0154] Carrier (e.g., hole or electron) mobility can provide an indication of how fast a carrier can move in a given electric field. In embodiments, the carrier mobility (e.g., electron mobility) of a given material can be measured by suitable known methods. In embodiments, the carrier mobility (e.g., electron mobility) can be measured by time of flight (TOF) methods, field effect mobility (FEM) methods, impedance spectroscopy, space charge limited current (SCLC) measurements, or combinations thereof.

[0155] Electron mobility of small molecule organic compounds (unit: cm 2 V -1 s -1 ) may be greater than or equal to about 1×10 -4 , greater than or equal to about 2.5×10 -4 , greater than or equal to approximately 4×10 -4 , greater than or equal to about 8×10 -4 , greater than or equal to about 1×10 -3 , greater than or equal to about 2.5×10 -3 , greater than or equal to approximately 4×10 -3 , greater than or equal to about 8×10 -3 , or greater than or equal to approximately 9×10 -3 .

[0156] Electron mobility of small molecule organic compounds (unit: cm 2 V -1 s -1 ) may be less than or equal to about 0.1, less than or equal to about 0.05, less than or equal to about 0.01, less than or equal to about 0.005, less than or equal to about 0.001, or less than or equal to about 0.0005.

[0157] Electron mobility of metal oxides (unit: cm 2 V -1 s -1 ) may be greater than or equal to about 1×10 -3 , greater than or equal to about 2.5×10 -3 , greater than or equal to approximately 4×10 -3 , greater than or equal to about 8×10 -3 , greater than or equal to about 1×10 -2 , greater than or equal to about 2.5×10 -2 , greater than or equal to approximately 4×10 -2 , greater than or equal to about 8×10 -2 , greater than or equal to about 1×10 -1 , greater than or equal to about 2.5×10 -1 , greater than or equal to approximately 4×10 -1 , greater than or equal to about 8×10 -1 , greater than or equal to about 1, greater than or equal to about 2.5, greater than or equal to about 4, greater than or equal to about 8, greater than or equal to about 10, greater than or equal to about 25, greater than or equal to about 40, or greater than or equal to about 80.

[0158] Electron mobility of metal oxides (unit: cm 2 V -1 s -1) may be less than or equal to about 1000, less than or equal to about 500, less than or equal to about 400, less than or equal to about 300, less than or equal to about 200, less than or equal to about 150, less than or equal to about 140, less than or equal to about 130, less than or equal to about 120, less than or equal to about 100, less than or equal to about 90, less than or equal to about 80, less than or equal to about 70, less than or equal to about 60, less than or equal to about 50, less than or equal to about 30, less than or equal to about 20 , less than or equal to about 10, less than or equal to about 9, less than or equal to about 8, less than or equal to about 7, less than or equal to about 6, less than or equal to about 5, less than or equal to about 3, less than or equal to about 2, less than or equal to about 1, less than or equal to about 0.9, less than or equal to about 0.8, less than or equal to about 0.7, less than or equal to about 0.6, less than or equal to about 0.5, less than or equal to about 0.4, less than or equal to about 0.3, less than or equal to about 0.2, or less than or equal to about 0.1.

[0159] The organic compound can be dissolved in a solvent (e.g., a polar organic solvent) used for the solution process of the metal oxide containing Zn, so the electron assisting layer according to the embodiment can be formed by a solution process, and the ratio of the small molecule organic compound and the metal oxide nanoparticles containing zinc can be adjusted at a desired ratio in the electron assisting layer.

[0160] As will be understood by one of ordinary skill in the art, the small molecule organic compound comprises carbon. The small molecule organic compound may have a molecular weight of less than or equal to about 2,000 grams per mole (g / mol), such as less than or equal to about 1,900 g / mol, less than or equal to about 1,800 g / mol, less than or equal to about 1,700 g / mol, less than or equal to about 1,600 g / mol, less than or equal to about 1,500 g / mol, less than or equal to about 1,400 g / mol, less than or equal to about 1,300 g / mol, less than or equal to about 1,200 g / mol, less than or equal to about 1,100 g / mol, or less than or equal to about 1,000 g / mol. The small molecule organic compound may have a molecular weight of greater than or equal to about 100 g / mol, such as greater than or equal to about 200 g / mol, greater than or equal to about 300 g / mol, greater than or equal to about 400 g / mol, greater than or equal to about 500 g / mol, greater than or equal to about 600 g / mol, greater than or equal to about 700 g / mol, or greater than or equal to about 800 g / mol. The small molecule organic compound may be soluble in a polar solvent (e.g., an alcohol such as ethanol).

[0161] The small molecule organic compound may not include halogens. The small molecule organic compound may not include metal ions. The small molecule organic compound may not include a diazole moiety (eg, a benzodiazole moiety), a quinoline moiety, a pyridine moiety, a carbazole moiety, or a combination thereof.

[0162] Without wishing to be bound by any theory, it is believed that the electron transport layer according to the embodiment can be formed by a solution process, so the small molecule organic compound can effectively fill the holes between the metal oxide nanoparticles containing Zn to provide improved uniformity. Without being bound by any theory, it is believed that the small molecule organic compound has an electron mobility lower than the electron mobility of the metal oxide containing Zn in the electron transport layer, the high leakage current of the metal oxide containing Zn can be reduced, and the excessive electron injection characteristics of the metal oxide containing Zn can be reduced or suppressed; and ZnO nanoparticles can compensate for the characteristics of the small molecule organic compound with low electron mobility. When only the small molecule organic compound is used, it may be difficult to achieve desirable electroluminescent properties in the quantum dot-based electroluminescent device. The small molecule organic compound can provide an electron transport layer together with the metal oxide nanoparticles containing zinc through a solution process, and the electron transport characteristics and adjustable energy levels can be controlled. As a result, the efficiency and life characteristics of the light-emitting device can be improved.

[0163] The small molecule organic compound may have an absolute value of a LUMO energy level greater than or equal to about 2.5 eV, for example, greater than or equal to about 2.6 eV, greater than or equal to about 2.7 eV, greater than or equal to about 2.8 eV, greater than or equal to about 2.82 eV, or greater than or equal to about 2.85 eV and less than or equal to about 3 eV, for example, less than or equal to about 2.95 eV, or less than or equal to about 2.9 eV.

[0164] The small molecule organic compound may have an absolute value of a HOMO energy level of greater than or equal to about 6.5 eV, for example, greater than or equal to about 7 eV, greater than or equal to about 7.1 eV, greater than or equal to about 7.2 eV, or greater than or equal to about 7.3 eV and less than or equal to about 8 eV, for example, 7.9 eV, less than or equal to about 7.8 eV, less than or equal to about 7.7 eV, less than or equal to about 7.6 eV, less than or equal to about 7.5 eV, or less than or equal to about 7.4 eV.

[0165] The electron mobility in the film including the small molecule organic compound, for example, composed of the small molecule organic compound, may be lower than the electron mobility in the film including the nanoparticle, for example, composed of the nanoparticle. The thickness of the film may be greater than or equal to about 20 nm and less than or equal to about 200 nm. The electron mobility may be measured by an appropriate method, which is not particularly limited.

[0166] The small molecule organic compound may include a compound including a triarylphosphine oxide moiety (eg, triphenylphosphine oxide) attached to an aromatic ring.

[0167] The small molecule organic compound may include a compound represented by Chemical Formula 2:

[0168] Chemical formula 2

[0169]

[0170] wherein Ar is a substituted or unsubstituted C6-C40 aryl group (e.g., a substituted or unsubstituted phenyl moiety), a substituted or unsubstituted C3-C40 heteroaryl group, or a substituted or unsubstituted C3-C40 heterocycloalkyl group (e.g., a substituted or unsubstituted triazine moiety or a substituted or unsubstituted triazinetrione moiety), or a combination thereof,

[0171] n is greater than or equal to 1, for example greater than or equal to 2, or greater than or equal to 3 and less than or equal to 10, for example less than or equal to 9, less than or equal to 8, less than or equal to 7, less than or equal to 6, less than or equal to 5, or less than or equal to 4.

[0172] The small molecule organic compound may include a compound represented by Chemical Formula 2-1:

[0173] Chemical formula 2-1

[0174]

[0175] wherein Ar is a substituted or unsubstituted C6-C40 aryl group (a substituted or unsubstituted phenyl moiety, or a substituted or unsubstituted naphthyl moiety), a substituted or unsubstituted C3-C40 heteroaryl group, or a substituted or unsubstituted C3-C40 heterocycloalkyl group (e.g., a substituted or unsubstituted triazine moiety, or a substituted or unsubstituted triazinetrione moiety), or a combination thereof.

[0176] In the electron assist layer, the carbon content relative to 1 mole of zinc may be greater than or equal to about 0.01 mole, for example, greater than or equal to about 0.02 mole, greater than or equal to about 0.03 mole, greater than or equal to about 0.04 mole, greater than or equal to about 0.05 mole, greater than or equal to about 0.1 mole, greater than or equal to about 0.2 mole, greater than or equal to about 0.3 mole, greater than or equal to about 0.4 mole, greater than or equal to about 0.5 mole, greater than or equal to about 0.6 mole, greater than or equal to about 0.7 mole, or greater than or equal to about 0.8 mole. In the electron auxiliary layer, the content of carbon relative to 1 mol of zinc may be less than or equal to about 20 mol, less than or equal to about 19 mol, less than or equal to about 18 mol, less than or equal to about 17 mol, less than or equal to about 16 mol, less than or equal to about 15 mol, less than or equal to about 14 mol, less than or equal to about 13 mol, less than or equal to about 12 mol, less than or equal to about 11 mol, less than or equal to about 10 mol, less than or equal to about 9 mol, less than or equal to about 8 mol, less than or equal to about 7 mol, less than or equal to about 6 mol, less than or equal to about 5 mol, less than or equal to about 4 mol, less than or equal to about 3 mol, less than or equal to about 2 mol, or less than or equal to about 1 mol. The electron auxiliary layer according to the embodiment can be formed using a solution process, as described above, and therefore, the mixing ratio of the nanoparticles of the metal oxide containing Zn and the small molecule organic compound can be easily controlled. The mixing ratio can be determined in consideration of the composition of the metal oxide, the type of the small molecule organic compound, the type of the hole auxiliary layer, the properties of the desired electron auxiliary layer, etc. As such, by controlling the mixing ratio, the amount of electrons injected into the quantum dot emission layer can be controlled, and thus optimization of the charge balance in the device can be achieved.

[0177] The thickness of the electron-assisted layer may be appropriately selected in consideration of the photoluminescence wavelength of the quantum dots, the thickness of the emission layer, the type and thickness of the hole-assisted layer, etc. In the device according to the embodiment, the quantum dots in the emission layer may emit light having a central wavelength of about 600 nm to about 640 nm, and the thickness of the electron-assisted layer may be greater than or equal to about 20 nm, such as greater than or equal to about 25 nm, greater than or equal to about 30 nm, greater than or equal to about 35 nm, greater than or equal to about 40 nm, or greater than or equal to about 45 nm and less than or equal to about 80 nm, such as less than or equal to about 75 nm, less than or equal to about 70 nm, less than or equal to about 65 nm, less than or equal to about 60 nm, or less than or equal to about 55 nm. In a device according to an embodiment, the quantum dots may emit light having a central wavelength less than or equal to about 500 nm, and the thickness of the electron-assisted layer may be greater than or equal to about 60 nm, for example, greater than or equal to about 65 nm, greater than or equal to about 70 nm, or greater than or equal to about 75 nm and less than or equal to about 120 nm, for example, less than or equal to about 115 nm, less than or equal to about 110 nm, less than or equal to about 105 nm, less than or equal to about 100 nm, less than or equal to about 95 nm, or less than or equal to about 90 nm.

[0178] The embodiment provides a method for manufacturing the aforementioned light-emitting device, comprising dispersing the nanoparticles and the small molecule organic compound in a polar organic solvent to prepare a dispersion; applying the prepared dispersion on an emission layer including quantum dots to form an electron-assisted layer; and removing the organic solvent from the electron-assisted layer.

[0179] The details of the nanoparticles and the small molecule organic compound are the same as described above. The specific method of forming the electrode and the hole auxiliary layer on the aforementioned substrate can be appropriately selected without particular limitation. The aforementioned hole auxiliary layer 12 and the aforementioned emission layer 13 can be formed, for example, by a solution process such as spin coating, slit coating, inkjet printing, nozzle printing, spraying, blade coating, or a combination thereof, but is not limited thereto. The manner of applying the electron auxiliary layer is not particularly limited, but can be appropriately selected.

[0180] The polar solvent may include a C1-C10 alcohol solvent such as ethanol, a C2-C20 sulfoxide solvent such as dimethyl sulfoxide, a C2-C20 amide solvent such as dimethylformamide, or a combination thereof.

[0181] In the dispersion, the content of the small molecule organic compound based on 100 parts by weight of the nanoparticles may be greater than or equal to 1 part by weight, for example greater than or equal to 5 parts by weight, greater than or equal to 10 parts by weight, greater than or equal to 15 parts by weight, or greater than or equal to 20 parts by weight.

[0182] In the dispersion, the content of the small molecule organic compound based on 100 parts by weight of the nanoparticles may be less than or equal to about 50 parts by weight, for example, less than or equal to about 40 parts by weight, less than or equal to about 35 parts by weight, less than or equal to about 30 parts by weight, less than or equal to about 25 parts by weight, or less than or equal to about 20 parts by weight.

[0183] Removing the organic solvent from the electron-assisting layer can be carried out, for example, under vacuum at a predetermined temperature (for example, a temperature greater than or equal to about 60°C, or greater than or equal to about 70°C and less than or equal to about 100°C, for example, less than or equal to about 90°C, less than or equal to about 80°C, or less than or equal to about 75°C), but is not limited thereto.

[0184] The embodiment provides an electronic device including the light emitting device. The electronic device can be applied to various electronic devices such as a display device or a lighting device.

[0185] Hereinafter, the embodiments are described in more detail with reference to Examples. However, these Examples are exemplary, and the present scope is not limited thereto.

[0186] Analytical methods

[0187] 1. Photoluminescence Analysis

[0188] The photoluminescence (PL) spectra of the prepared nanocrystals were obtained using a Hitachi F-7000 spectrometer at a radiation wavelength of 372 nanometers (nm).

[0189] 2. Ultraviolet-visible (UV-Vis) spectroscopy analysis

[0190] UV spectroscopy analysis and UV-visible absorption spectra were obtained using a Hitachi U-3310 spectrometer.

[0191] 3.TEM analysis

[0192] Transmission electron micrographs of the nanocrystals were obtained using a UT F30Tecnai electron microscope.

[0193] 4. X-ray diffraction (XRD) analysis

[0194] XRD analysis was performed using a Philips XPert PRO instrument with a power of 3 kilowatts (kW).

[0195] 5. Electroluminescence spectroscopy analysis

[0196] A Keithley 2635B source meter was used to measure a current depending on a voltage while applying a voltage, and a CS2000 spectrometer was used to measure the electroluminescence (EL) emission brightness.

[0197] Synthesis of quantum dots

[0198] Reference Example 1: Preparation of quantum dots emitting red light

[0199] (1) 0.2 millimole (mmol) of indium acetate was dissolved in a 300 milliliter (mL) reaction flask containing 1-octadecene together with palmitic acid and heated at 120° C. under vacuum. After 1 hour, the atmosphere in the reactor was changed to nitrogen. After heating at 280° C., a mixed solution of tri(trimethylsilyl)phosphine (TMS3P) and trioctylphosphine was quickly injected and reacted for 30 minutes. Acetone was added to the reaction solution that had been rapidly cooled to room temperature and it was centrifuged to provide a precipitate, and the obtained precipitate was dispersed in toluene.

[0200] Se powder and S powder were dissolved in trioctylphosphine (TOP) to prepare Se / TOP stock solution (stock solution) and S / TOP stock solution.

[0201] Indium acetate and oleic acid were dissolved in trioctylamine in a 300 mL reaction flask and vacuum treated at 120° C. for 10 minutes. The flask was purged with nitrogen (N 2 ) and then heated at 180°C.

[0202] The obtained InP cores were added and reacted at a reaction temperature of 280° C. for 60 minutes while adding a predetermined amount of the Se / TOP stock solution and a predetermined amount of the S / TOP stock solution.

[0203] Excess ethanol is added to the reactant including semiconductor nanocrystals, and then centrifuged. After centrifugation, the supernatant is discarded, the precipitate is dried, and then dispersed in chloroform or toluene to provide a quantum dot solution (hereinafter, QD solution). The UV-Vis absorption spectrum of the obtained QD solution is measured. The obtained quantum dots emit red light.

[0204] Reference Example 2: Preparation of quantum dots emitting blue light

[0205] (1) Selenium (Se) and tellurium (Te) were dispersed in trioctylphosphine (TOP) to obtain a 2 M Se / TOP stock solution and a 0.1 M Te / TOP stock solution.

[0206] 0.125 mmol of indium acetate was added together with oleic acid to a reactor including trioctylamine and the solution was heated under vacuum at 120° C. After one hour, the atmosphere in the reactor was switched to nitrogen.

[0207] Subsequently, the reactor was heated to 300°C, and the prepared Se / TOP stock solution and Te / TOP stock solution were rapidly injected therein at a Te / Se ratio of 1 / 25. When the reaction was completed, acetone was added to the reaction solution rapidly cooled to room temperature, and the precipitate obtained by centrifugation was dispersed in toluene to obtain ZnTeSe quantum dots.

[0208] (2) 1.8 mmol (0.336 grams (g)) of indium acetate was added to a flask containing trioctylamine together with oleic acid and vacuum treated at 120° C. for 10 minutes. The flask was filled with nitrogen (N 2 ) and the temperature was raised to 180° C. The obtained ZnTeSe core was added thereto, and the reaction was carried out at a reaction temperature of about 280° C. while Se / TOP and S / TOP were added. After the reaction was completed, the reactor was cooled, and the prepared nanocrystals were centrifuged with ethanol and dispersed in toluene to obtain ZnTeSe / ZnSeS core / shell quantum dots.

[0209] Synthesis of Metal Oxide Nanoparticles

[0210] Reference Example 3: Synthesis of ZnO

[0211] Indium acetate dihydrate was added to a reactor including dimethyl sulfoxide and heated at 60°C under air. Subsequently, 15 mmol of tetramethylammonium hydroxide pentahydrate was dissolved in 30 mL of ethanol and added dropwise to the reactor at 3 mL. After stirring it for 1 hour, the obtained ZnO nanoparticles and ethyl acetate were centrifuged at a ratio (volume ratio) of 1:9 and dispersed in ethanol to obtain ZnO nanoparticles.

[0212] The obtained nanoparticles were subjected to X-ray diffraction analysis to confirm the formation of ZnO crystals. Transmission electron microscopy analysis was performed on the obtained nanoparticles, and the results showed that the particles had an average size of about 3 nm.

[0213] The energy band gap of the obtained nanoparticles was measured and monitored by UV band edge tangent (UV-2600, SHIMADZU). The results showed that the synthesized ZnO had an energy band gap of about 3.52 eV.

[0214] Manufacturing of light-emitting devices

[0215] Example 1

[0216] The glass substrates on which indium tin oxide (ITO) was deposited were treated with UV-ozone for 15 min, then spin-coated with poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) solution (HC Starks) and heated at 150 °C for 10 min in air atmosphere, and then placed under N 2 The mixture was heat treated again at 150° C. for 10 minutes under an atmosphere to provide a hole injection layer having a thickness of 30 nm. Subsequently, a poly[(9,9-dioctylfluorene-2,7-diyl-co(4,4′-(N-4-butylphenyl)diphenylamine] solution (TFB) (Sumitomo) was spin-coated on the hole injection layer and heated at 150° C. for 30 minutes to provide a hole transport layer having a thickness of 25 nm.

[0217] The core / shell quantum dots obtained from Reference Example 1 were spin-coated on the obtained hole transport layer and heated at 80° C. for 30 minutes to provide an emission layer having a thickness of 25 nm.

[0218] A solution of ZnO nanoparticles obtained in Reference Example 3 was prepared (solvent: ethanol, optical density: 0.5 arbitrary unit (au)). A small molecule organic compound solution (concentration: 2 weight percent (wt%)) was prepared by dissolving a small molecule organic compound (2,4.6-tris[3-(diphenylphosphinoyl)phenyl]-1,3,5-triazine (PO-T2T)) having the following chemical formula in ethanol:

[0219]

[0220] The solution for the electron transport layer was obtained by mixing the prepared solution (with a weight ratio of nanoparticles: small molecule organic compound = 5:1). The obtained solution was spin-coated on the emission layer and heated at 80°C for 30 minutes to provide an electron auxiliary layer having a thickness of 50nm. 90nm aluminum (Al) was vacuum deposited on the obtained electron auxiliary layer to provide a second electrode to obtain a light-emitting device.

[0221] The electroluminescent properties of the obtained quantum dot light-emitting device were evaluated using a Keithley 2200 source meter and a Minolta CS2000 spectroradiometer (current-voltage-brightness measuring device). Specifically, the current, brightness, and electroluminescence (EL) depending on the voltage applied to the device were measured by the current-voltage-brightness measuring device, and the external quantum efficiency was calculated therefrom.

[0222] The results are shown in Table 1. Figure 2 and 3 middle.

[0223] In this embodiment, the electron mobility of zinc oxide particles and the electron mobility of the above small molecule organic compound were measured by using the FEM method and the TOF method, respectively. The results confirmed that the electron mobility of the above small molecule organic compound was lower than that of zinc oxide particles.

[0224] Comparative Example 1-1

[0225] A light emitting device was obtained according to the same procedure as in Example 1, except that the small molecule organic compound (PO-T2T) was not used.

[0226] The electroluminescence of the obtained light-emitting device was evaluated according to the same procedure as in Example 1.

[0227] The results are shown in Table 1. Figure 2 and 3 middle.

[0228] Comparative Example 1-2

[0229] A light emitting device was obtained according to the same procedure as in Example 1, except that ZnO was not used. The electroluminescent properties of the obtained light emitting device were evaluated according to the same procedure as in Example 1.

[0230] Table 1

[0231]

[0232] *Max.EQE: Maximum (max.) external quantum efficiency

[0233] *EQE@100 nits: External quantum efficiency at a brightness of 100 nits (cd / m²)

[0234] *Max.Cd / A (candela / ampere): maximum current efficiency

[0235] *λmax.: Maximum photoluminescence wavelength

[0236] *Max.Lum.: Maximum brightness

[0237] From Table 1 and Figure 2 The results of , confirm that the device according to Example 1 can show improved efficiency and improved brightness compared to the device according to Comparative Example 1-1. Figure 3 From the results, it was confirmed that the device according to Example 1 showed a greatly reduced leakage current compared to the device according to Comparative Example 1-1.

[0238] Example 2

[0239] A light-emitting device was obtained according to the same procedure as in Example 1, except that the blue light-emitting quantum dots synthesized by Reference Example 2 were used instead of the red light-emitting quantum dots, and a small molecule organic compound (1,3,5-tris[3-(diphenylphosphoryl)phenyl]benzene (TP3PO)) having the following structure was used instead of PO-T2T, and a layer thickness of 50 nm was adopted as follows:

[0240]

[0241] The electroluminescence of the obtained light-emitting device was evaluated according to the same procedure as in Example 1.

[0242] The results are shown in Table 2. Figure 4 and 5 middle.

[0243] In this embodiment, the electron mobility of zinc oxide particles and the electron mobility of the above small molecule organic compound were measured by using the FEM method and the TOF method, respectively. The results confirmed that the electron mobility of the above small molecule organic compound was lower than that of zinc oxide particles.

[0244] Comparative Example 2-1

[0245] A light-emitting device was obtained according to the same procedure as in Example 2, except that the small molecule organic compound (TP3PO) was not used.

[0246] The electroluminescent properties of the obtained light-emitting device were evaluated according to the same method as in Example 1.

[0247] The results are shown in Table 2. Figure 4 and 5 middle.

[0248] Comparative Example 2-2

[0249] A light emitting device was obtained according to the same procedure as in Example 2, except that ZnO was not used, and an organic compound PO-T2T was used. The electroluminescent properties of the obtained light emitting device were evaluated according to the same method as in Example 1. The results are shown in Tables 2 and Figure 6 middle.

[0250] Comparative Examples 2-3

[0251] A light emitting device was obtained according to the same procedure as in Example 2, except that ZnO was not used. The electroluminescent properties of the obtained light emitting device were evaluated according to the same method as in Example 1. The results are shown in Tables 2 and Figure 6 middle.

[0252] Table 2

[0253]

[0254] From Table 2 and Figure 4 The results of , confirm that the device according to Example 2 shows improved efficiency and improved brightness compared to the devices according to Comparative Examples 2-1, 2-2, and 2-3. Figure 5 From the results, it was confirmed that the device according to Example 2 showed a greatly reduced leakage current compared to the device according to Comparative Example 2-1.

[0255] Experimental Example 1

[0256] When a constant current driven at 100 nits was applied to the devices according to Example 1 and Comparative Example 1-1, the time (hours) until the luminance reached 95% of the initial luminance relative to 100% (T95 (h)) and the time (hours) until the luminance reached 50% of the initial luminance relative to 100% (T50 (h)) were evaluated. As shown in the results, it was confirmed that the device according to Example 1 showed a T95 (h) improved by two times and a T50 (h) improved by 1.5 times relative to the device according to Comparative Example 1-1.

[0257] While the present disclosure has been described with respect to what are presently considered to be practical example embodiments, it is to be understood that the invention is not limited to the disclosed embodiments, but on the contrary is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.

[0258] Explanation of symbols

[0259] 10: Light-emitting devices

[0260] 11: First electrode

[0261] 12: Hole auxiliary layer

[0262] 13: Emission layer

[0263] 14: Electronic auxiliary layer

[0264] 15: Second electrode

Claims

1. Light-emitting devices, including a first electrode and a second electrode facing each other, an emission layer disposed between the first electrode and the second electrode, the emission layer comprising quantum dots, and an electron auxiliary layer disposed between the emission layer and the second electrode, the electron auxiliary layer comprising a mixture of nanoparticles and small molecule organic compounds, wherein the nanoparticles include a metal oxide comprising zinc, and The electron mobility of the small molecule organic compound is smaller than the electron mobility of the nanoparticles, The small molecule organic compound includes a compound represented by Chemical Formula 2-1: Chemical formula 2-1 in, Ar is a substituted or unsubstituted C6-C40 aryl group, a substituted or unsubstituted C3-C40 heteroaryl group, a substituted or unsubstituted C3-C40 heterocycloalkyl group, or a combination thereof. 2 . The light emitting device according to claim 1 , wherein a work function of the first electrode is greater than a work function of the second electrode. The light emitting device of claim 1 , wherein the first electrode comprises indium tin oxide. The light emitting device of claim 1 , wherein the second electrode comprises a conductive metal. The light emitting device of claim 1 , wherein the quantum dots do not include cadmium. The light emitting device of claim 1 , wherein the quantum dots comprise indium and phosphorus. The light emitting device of claim 1 , wherein the quantum dots comprise chalcogen and zinc. 8 . The light emitting device according to claim 1 , wherein an absolute value of a lowest unoccupied molecular orbital energy level of the quantum dot is smaller than an absolute value of a lowest unoccupied molecular orbital energy level of the metal oxide.

9. The light emitting device according to claim 1, wherein the metal oxide is represented by Chemical Formula 1: Chemical formula 1 Zn 1-x M x O in, In Chemical Formula 1, M is Mg, Ca, Zr, W, Li, Ti, Y, Al, or a combination thereof, and 0≤x≤0.5。 10. The light emitting device of claim 1, wherein the metal oxide comprises zinc oxide, magnesium zinc oxide, or a combination thereof. The light emitting device according to claim 1 , wherein an average size of the nanoparticles is greater than or equal to 1 nanometer and less than or equal to 10 nanometers. 12 . The light emitting device of claim 1 , wherein an average size of the nanoparticles is greater than or equal to 1.5 nanometers and less than or equal to 5 nanometers.

13. The light emitting device according to claim 1, wherein the small molecule organic compound has the absolute value of the lowest unoccupied molecular orbital energy level greater than or equal to 2.5 electron volts and less than or equal to 3 electron volts, and The absolute value of the highest occupied molecular orbital energy level greater than or equal to 7 electron volts and less than or equal to 7.5 electron volts.

14. The light emitting device of claim 1, wherein electron mobility in a thin film including the small molecule organic compound is lower than electron mobility in a thin film including the nanoparticles. 15 . The light emitting device of claim 1 , wherein in the electron assisting layer, the small molecule organic compound fills holes between the nanoparticles. 16 . The light emitting device according to claim 1 , wherein in the electron assist layer, a content of carbon relative to 1 mol of zinc is greater than or equal to 0.01 mol. 17 . The light emitting device according to claim 1 , wherein in the electron assist layer, a content of carbon is less than or equal to 20 mol relative to 1 mol of zinc.

18. The light emitting device of claim 1, wherein the quantum dots emit light having a central wavelength of 600 nanometers to 640 nanometers, and a thickness of the electron assisting layer is greater than or equal to 20 nanometers and less than or equal to 50 nanometers.

19. The light emitting device of claim 1, wherein the quantum dots emit light having a central wavelength less than or equal to 500 nanometers, and the thickness of the electron assist layer is greater than or equal to 60 nanometers and less than or equal to 100 nanometers.

20. The light emitting device of claim 1, wherein Ar is a substituted or unsubstituted phenyl moiety, a substituted or unsubstituted naphthyl moiety, a substituted or unsubstituted triazine moiety, or a substituted or unsubstituted triazinetrione moiety.

21. A method for manufacturing a light emitting device according to any one of claims 1 to 20, comprising: dispersing the nanoparticles and the small molecule organic compound in a polar organic solvent to prepare a dispersion; applying the dispersion onto an emissive layer comprising quantum dots to form an electron assisting layer; and The polar organic solvent is removed from the electron assisting layer.

22. The method of claim 21, wherein the organic solvent comprises an alcohol solvent, a sulfoxide solvent, an amide solvent, or a combination thereof. 23 . The method of claim 21 , wherein in the dispersion, the content of the small molecule organic compound is greater than or equal to 1 part by weight and less than or equal to 50 parts by weight based on 100 parts by weight of the nanoparticles.

24. A display device comprising the light emitting device according to any one of claims 1 to 20.

Citation Information

Patent Citations

  • Hybrid two step cleaning apparatus using multistage deodorising filter

    KR1020180083061A

  • Highly lumminescent nanostructures and methods of producing same

    CN104520228A

  • Semiconducting material comprising a phosphine oxide matrix and metal salt

    CN106104832A

  • Quantum dot light-emitting device and display device and lighting device with same

    CN106654026A